Avaliação da eficiência de combustão de carvão de PCI, em diferentes taxas de injeção, aplicada ao Alto-forno A da ArcelorMittal Monlevade - Leonardo Francisco Berçot (2022)
This study aims to establish a methodical procedure for evaluating the combustion efficiency of coal or PCI coal mix injected into the tuyeres of ArcelorMittal Monlevade's Blast Furnace A. For this, dust samples were collected at the top of the referred blast furnace for further thermogravimetric analysis, which has the purpose of separating the different types of carbon, which originate from metallurgical coke and a possible portion of coal injected into the tuyeres and not burned inside. of the reactor. Through the experiments carried out, it was possible to conclude that there was no significant loss of combustion efficiency for the work ranges normally applied to ArcelorMittal Monelvade's Blast Furnace A, whose values are between 160 to 180 kg/t. The greatest loss of efficiency occurred when comparing the injection rate extremes analyzed in the present work, namely: 130 and 185 kg/t, between these two scenarios, an increase in the carbon content originating from PCI coal of approximately 2 kg/t, low value, when compared to the benefits of productivity gain and cost reduction of pig iron production brought in the operation with higher injection rate. The results found are consistent with technical publications in the scientific community, where it is mentioned that the loss of combustion efficiency becomes significant for PCI coal injection rates above 190 kg/t. Finally, the procedure adopted may be used for analysis at the Monlevade plant when new coals are used, mixtures of different fuels and/or operations with higher injection rates compared to those currently practiced.